The basic criteria for the development of architectural education programs - Mustafa Kamil Kadhim (Iraqi Journal of Architecture and Planning, 2018)
Many of architectural schools experiencing challenges related to the weakness of their suitability to meet the standards of the criditability inistitutions. In reaction to that, interest increased about quality and cridibility to ensure that the educational process outputs meet with the requirements of international recognition. The problem of the search to find the deficient in the diagnosis of the factors affecting the development of architectural education programs and enter the quality and cridibility as new variables concepts. The objective of the research identifying factors affecting the development of architectural education programs and proposing the changes necessary to make the development process in line with the recent developments and the increased informational base from a global point of cridibility and  international standards on the other hand.